Gambaran Tingkat Pengetahuan, Pengalaman Dan Dukungan Suami Dalam Penggunaan Kontrasepsi Di Desa Bendosari Kabupaten Boyolali - Widyastiwi, Inesti Dewi, H.M. Abi Muhlisin, SKM., M.Kep, Dian Nur W, S.Kep., Ns (2016)
The use of contraceptives is a shared responsibility between men and women as a pair, so the method of contraception that will be selected in accordance with the needs and desires together. Some of the factors that influence the use of contraception is the knowledge, the support of her husband and family planning experience. This study aims to describe the level of knowledge, experience and support their husbands in the use of contraception in the village Bendosari Boyolali. This research is descriptive. Sample study was 67 couples of childbearing age who have ever used contraception in the village Bendosari Sawit Subdistrict Boyolali with proportional random sampling technique. Data collection was obtained from a questionnaire study. Data analysis was performed using univariate analysis. Research shows that the mother's knowledge couples of childbearing age about contraception is largely adequate, experience in the use of contraception in women of fertile couples contraceptive users are mostly good, and husband support the use of contraception in women of fertile couples Bendosari contraceptive users in the village of Boyolali mostly do not support. Keywords: knowledge, experience, support the husband, the use of contraceptive